2019
DOI: 10.3390/rs11222685
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Reforestation in the Loess Plateau, China after the “Grain for Green” Project through Integrating PALSAR and Landsat Imagery

Abstract: An unprecedented reforestation process happened in the Loess Plateau, China due to the ecological restoration project ‘Grain for Green Project’, which has affected regional carbon and water cycles as well as brought climate feedbacks. Accurately mapping the area and spatial distribution of emerged forests in the Loess Plateau over time is essential for forest management but a very challenging task. Here we investigated the changes of forests in the Loess Plateau after the forest reconstruction project. First, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…LAI data attest to an obvious increase in vegetation greening on the LP during 1995-2015 (increase rate: 0.008 m 2 m −2 yr −1 ), and the area of a new leaf was increased by 1.23 × 10 5 km 2 . Several previous studies confirm this vegetation greening trend (Wang et al, 2015;Zhou et al, 2019). Overall, the above results can be attributed to large-scale vegetation restoration projects, intensified agriculture, and climate factor (Kou et al, 2021;Schwarzel et al, 2020).…”
Section: The Drivers Of Vegetation Greening On the Lpsupporting
confidence: 77%
“…LAI data attest to an obvious increase in vegetation greening on the LP during 1995-2015 (increase rate: 0.008 m 2 m −2 yr −1 ), and the area of a new leaf was increased by 1.23 × 10 5 km 2 . Several previous studies confirm this vegetation greening trend (Wang et al, 2015;Zhou et al, 2019). Overall, the above results can be attributed to large-scale vegetation restoration projects, intensified agriculture, and climate factor (Kou et al, 2021;Schwarzel et al, 2020).…”
Section: The Drivers Of Vegetation Greening On the Lpsupporting
confidence: 77%
“…We found that the proportion of artificial restoration in Wuqi was the highest of all areas within the study region, which is supported by previous research. For instance, Sun et al (2015) and Liu et al (2020) found that the area and investment involved in the GFGP in northern Shaanxi were much higher than the average for the Loess Plateau; Liu et al (2020) and Zhou et al (2019) reported that the implementation intensity of the GFGP in Yan'an was significantly greater than that in Yulin and that it was even higher in Wuqi. The GFGP is a top-down regulatory policy (Meyer et al, 2018;Zhang et al, 2008), and the annual tasks for the GFGP are transmitted stepwise along with administrative levels (Xu & Zhang, 2021).…”
Section: Adjustment Effects Of Climate Factorsmentioning
confidence: 99%
“…However, most previous studies have focused on areas with dense forest vegetation. [6] This study aims to explore the applicability of forest information acquisition methods based on decision-level fusion and feature-level fusion of multi-source remote sensing data in areas with low forest coverage and scattered vegetation. Select the Yellow River Basin (Gansu Section) as the research object, compare and verify the accuracy of the classification results of the two methods, and obtain a high-precision forest information extraction method suitable for this research area, which is an evaluation of the ecological engineering effect of the Yellow River Basin (Gansu Section) A high-precision basic data collection method is provided.…”
Section: Introductionmentioning
confidence: 99%